P-567 Recombinant hCG (choriogonadotropin beta, CG beta) exerts a positive dose-dependent effect on human follicular steroidogenesis during ovarian stimulation using a constant rFSH administration. (30th June 2022) - Bøtkjær, J.A; Kristensen, S.G; Olesen, H.Ø; Larsson, P; Mannaerts, B; Yding Andersen, C
Abstract: Study question: How does increasing doses of CG beta augment follicular steroidogenesis and is it associated with gene expression in cumulus cells? Summary answer: With the exception of progesterone, CG beta exerts dose-dependent effects on intrafollicular steroid hormone concentrations and CYP19a1 expression during constant rFSH administration. What is known already: CG beta (FE 999302) is a newly developed rhCG, produced by a human cell line (PER.C6 ® ). This variant contains the same amino acid sequence as the endogenous hCG but presents with a different glycosylation profile when compared to urinary hCG or rhCG derived from a CHO cell line. CG beta has also been shown to have a longer half-life and higher relative potency. It is well known that hCG like LH creates an intracellular response through the LHR expressed on theca cells and mature granulosa cells and hereby augment the production of androgens, progesterone, and oestrogen. Study design, size, duration: This study is part of a randomised, double-blind, placebo-controlled trial to investigate the efficacy and safety of CG beta as an add-on treatment to rFSH in women undergoing ovarian stimulation during a long GnRH agonist protocol. The primary endpoint of this study was intrafollicular steroid levels in relation to CG beta administration. Secondary outcomes were gene expression of LHR, FSHR, CYP19a1, and androgen receptor (AR) and single nucleotide polymorphisms (SNPs) in LHR(312) and FSHR(307). Participants/materials, setting, methods: 619 women with AMH levels 5-35 pmol/L were randomized to receive either placebo or 1, 2, 4, 8, or 12 µg CG beta from day one of stimulation combined with a constant individualized dose of rFSH. Follicular fluid (FF) (n = 558), granulosa (n = 498) and cumulus cells (n = 368) were collected at oocyte retrieval. Steroid FF hormones were measured using ELISAs, gene expression was analysed in cumulus cells by qRT-PCR, and SNP analysis was performed in granulosa cells. Main results and the role of chance: This study found that CG beta has a pronounced positive dose-dependent effect on intrafollicular concentrations of 17-OH-progesterone, androstenedione, testosterone, and oestradiol during constant rFSH administration. As compared to the placebo group without CG beta administration the concentrations of steroids were significantly dose-dependently increased (p-value<0.0001) reaching up to 10 times higher values in the highest dose group without a clear plateauing. However, for progesterone, there was no statistically significant difference between the CG beta dose groups and placebo. The gene expression level of CYP19a1 in the cumulus cells collected at oocyte retrieval increased significantly (p-value=0.0325) for the highest dose of CG beta. However, the gene expression level of FSHR, LHR, and AR in cumulus cells were not affected by CG beta administration, as no dose-response trend with increasing dose of CG beta was observed. Additionally, this study revealed that there was no overall clear difference in the number of oocytes retrieved between the different CG beta dose groups based on either the FSHR(307) or LHR(312) genotypes. Limitations, reasons for caution: The gene expression was assessed in cumulus cells, but it would also have been interesting to evaluate the mural granulosa cells. Analysis of the gene expression of 3βHSD and other important steroidogenic enzymes in the mural granulosa cells could reveal further explanation to the effect of CG beta administration. Wider implications of the findings: To our knowledge, this is the first study to show a clear dose-dependent effect of rhCG on human steroidogenesis during constant rFSH administration in preovulatory follicles. This reflects the importance of the combined effect of FSH and hCG/LH on granulosa cell activity, follicle health, and potentially oocyte quality. Trial registration number: 000289